2018
DOI: 10.1149/2.0351811jss
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrochemical Behavior of Aluminum Chemical Mechanical Polishing at Low Down Pressure in Environmentally Friendly and Weakly Alkaline Slurry

Abstract: The lower pressure tendency in chemical mechanical polishing (CMP) process requires a lower adhesive inhibitor with environmentally friendly corrosion properties to replace the conventional benzotriazole (BTA) inhibitor for aluminum (Al) CMP. Open circuit potential test, potentiodynamic polarization curve test, linear sweep voltammetry and potential drop investigated by in-situ electrochemical mechanical polishing (ECMP) platform were used to reveal the controlled evolution process of corrosion inhibitor films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Therefore, the mild alkaline polishing slurry is desirable for the CMP of Al alloy. [17][18][19] According to the obtained experimental results, the pH of the polishing slurry was determined at 10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the mild alkaline polishing slurry is desirable for the CMP of Al alloy. [17][18][19] According to the obtained experimental results, the pH of the polishing slurry was determined at 10.…”
Section: Resultsmentioning
confidence: 99%
“…16 In order to solve the problems of equipment corrosion and environmental pollution of acidic polishing fluid, it is desirable to conduct CMP in alkaline polishing slurry. 17,18 Previous studies indicated high material removal rate (MRR) and good surface quality can be obtained in alkaline polishing slurry. [19][20][21] In the CMP of aluminum alloy, oxidant and complexing agents are critical additives, which have significant impact on material removal and surface quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HKMG process is divided into two camps: the Gate first process represented by IBM and the Gate last process represented by Intel in the semiconductor industry. 5,6 HKMG Gate last process is the mainstream process route of HKMG process; 7 The manufacturing technology of metal gate structure is the key technology of HKMG back gate process; 8 The chemical-mechanical polishing (CMP) technology of metal gate is a breakthrough in the upgrading of HKMG process technology, 9,10 and mainly refers to the CMP technology of Al gate in the back-gate process, and the CMP technology of Al gate will become an important breakthrough in the future patent layout and technology upgrading in this field. 11,12 Compared with polysilicon gates, [13][14][15] Al gates have good conductivity, provide a stronger gate electric field, and effectively reduce gate capacitance.…”
mentioning
confidence: 99%
“…2 As the feature size shrinks down to 28 nm and below, aluminum (Al) is commonly used in front-end-of-line (FEOL) structures as a feasible gate material. 5,6 Damage-free and atomically smooth surface of Al is required in the "gate-last" integration scheme for HKMG transistors. In addition, in the fabrication process of FinFET devices, the RMG gate material includes tungsten (W), aluminum (Al), nickel (Ni), cobalt (Co), and titanium (Ti).…”
mentioning
confidence: 99%